Enhancing responsivity of silicon PIN photodiodes at 1064 nm via light trapping and geometry optimization: a simulation study - Alghannam, Fahad; Alharthi, Nada S.; Alayed, Mrwan (Frontiers in Physics, 2025)
Nd:YAG laser light detection at 1064 nm is widely used in applications requiring high-performance photodiodes to measure low light intensities. This study investigates the impact of light trapping and geometric variations on the responsivity of silicon-based PIN photodiodes at 1064 nm. Simulations using Ansys Lumerical FDTD and CHARGE reveal several key findings. Without diffuse reflectors, the responsivity of the photodiodes aligns with theoretical and literature values of approximately 0.4–0.45 A/W. When rear-side diffuse reflectors are used, larger photodiode dimensions result in higher responsivity, with a peak of 0.58 A/W for photodiodes with a 400 µm thickness. Our simulations suggest that combining light trapping with optimized geometries or side reflectors could surpass the current responsivity ceiling of ∼0.57 A/W, offering a pathway to exceed this limit without sacrificing electrical performance. Also, light trapping reduces the required thickness of Si PIN photodiodes for achieving specific responsivity at 1064 nm. For instance, 100 µm thick photodiodes with diffuse reflectors exhibit a responsivity of approximately 0.31 A/W, compared to 0.28 A/W in 400 µm thick photodiodes without reflectors. However, the enhancement from light trapping diminishes as photodiode thickness increases. Optimal photodiode dimensions for balanced performance are suggested to be a thickness of 200–300 μm and an area of 0.6–2.5 mm2. Experimental validation is recommended to assess texturing-related effects, such as increased dark current or recombination.